Dynamics of unimolecular dissociation of silylene - Ibrahim Ali , Noorbatcha; L.M., Raff; D.L, Thompson; R., Viswanathan (American Institute of Physics (AIP), 1986)
The semiempirical valence‐bond surface formulated by Viswanathan e t a l. [J. Phys. Chem. 8 9, 1428 (1985)] for the unimolecular dissociation of SiH2 has been fitted to an analytical function of the type suggested by Murrell and co‐workers [J. Phys. Chem. 8 8, 4887 (1984)]. The fitted surface accurately represents most of the experimental and CI results. The dynamics of the unimolecular dissociation of SiH2 to form Si and H2 have been investigated by classical trajectory methods on this fitted surface. The effect of describing the initial state of the molecule using normal and local mode approximations has been studied. In spite of the presence of the heavier atom, no bond or mode specificity is observed. The product energy distribution is found to be statistical. Using the RRK model, the high‐pressure limiting rate coefficient is found to be k(T,∞)=3.38×101 2 exp[−61.6 kcal mol− 1/RT] s− 1, which is less than the dissociation rate for SiH4. This has been attributed to the higher activation energy for SiH2 and to a statistical factor.